Ethyl (E)-2-methoxyimino-2-(4-nitrobenzoyl)acetate - Caracelli, I.; Moran, P.J.S.; Hinoue, L.; Zukerman-Schpector, J.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title molecule, C(12)H(12)N(2)O(6), features an E conformation about the oxime group. The methoxyimino and ester residues are effectively coplanar with each other (r.m.s. deviation for the nine non-H atoms = 0.127 angstrom) and almost orthogonal [with dihedral angles of 99.44 (13) and - 77.85 (13)degrees, respectively] to the carbonyl and nitrophenyl groups which lie to either side of this central plane. The crystal structure is consolidated by C-H center dot center dot center dot O contacts.